2018
DOI: 10.1111/jomf.12538
|View full text |Cite
|
Sign up to set email alerts
|

Patrilocal, Matrilocal, or Neolocal? Intergenerational Proximity of Married Couples in China

Abstract: Objective:The study describes current patterns of intergenerational proximity in China and analyzes the structural conditions that are associated with couples' proximity to the husband's and the wife's parents. Background: Patrilocality is a core aspect of the traditional Chinese kinship system and is deeply rooted in Confucian beliefs. In recent decades, however, this custom has been challenged by internal migration as well changes in family values and preferences. Method: The authors model the effect of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…moving to their husbands' families as new members, whose position in the marital household was contingent upon their performance of 'virtuous' feminine duties as wives, daughters-in-law, siblings-in-law, and more importantly upon their reproduction of 'male offspring to assure continued ancestor worship' (Goode 1970, 275). Despite dramatic progress in women's socioeconomic position and increasing conjugal power in the post-reform era, the custom of patrilocal residence demonstrates a remarkable resilience in China, as national statistics show that the majority of married couples live within closer proximity to the patrilineal side (Gruijters and Ermisch 2019). Indeed, while my interviewees and their husbands generally established their separate households, over half indicated that their parents-in-law were more intimately involved in their everyday lives due to closer living arrangements.…”
Section: Not An Option: Modern Women's Traditional Guiltmentioning
confidence: 99%
“…moving to their husbands' families as new members, whose position in the marital household was contingent upon their performance of 'virtuous' feminine duties as wives, daughters-in-law, siblings-in-law, and more importantly upon their reproduction of 'male offspring to assure continued ancestor worship' (Goode 1970, 275). Despite dramatic progress in women's socioeconomic position and increasing conjugal power in the post-reform era, the custom of patrilocal residence demonstrates a remarkable resilience in China, as national statistics show that the majority of married couples live within closer proximity to the patrilineal side (Gruijters and Ermisch 2019). Indeed, while my interviewees and their husbands generally established their separate households, over half indicated that their parents-in-law were more intimately involved in their everyday lives due to closer living arrangements.…”
Section: Not An Option: Modern Women's Traditional Guiltmentioning
confidence: 99%
“…Daughters are now as likely as sons to provide financial support to parents in China, at least in urban areas (Hu 2017; Lei 2013; Xie and Zhu 2009). Parents living with sons is still dominant, but there are signs that norms of patrilocal residence are eroding (Gruijters and Ermisch 2019; Chen 2005; Chen and Short 2008; Xie and Zhu 2009). To my knowledge though, no studies have assessed if the growth of sonless families contributed to such broader changes.…”
Section: Background and Conceptualizationmentioning
confidence: 99%
“…There are three main ways in which matrilocal residence norms (or local post-marital residence norms more generally) affect the tradeoff that otherwise identical intermarried men and women face between retaining their original ethnicity vs. adopting a specific alternative ethnic identity, i.e., the ethnicity of their spouse. First, for newly intermarried men, 4 The literature distinguishes two other norms on post-marital residence, patrilocality and neolocality (Gruijters and Ermisch 2019;Holden et al 2003). Patrilocal norms prescribe that, after their marriage, couples will live at the (parents of the) grooms' place.…”
Section: Iiia1 Intermarriage Matrilocality and Spousal Ethnic Admentioning
confidence: 99%